Preparation and In vitro Evaluation of Orally Disintegrating Tablets (ODTs) of Alprazolam (Dhaka University Journal of Pharmaceutical Sciences, 2019)
Abstract not availableDhaka Univ. J. Pharm. Sci. 18(1): 129-133, 2019 (June)